A2_2 What If It's Always Sunny In Philadelphia? - Moore, J.; Davies, C. T.; Cheshire, K. J.; Garratley, R. (Physics Special Topics, 2016)
We calculate the solar flux that would reach Philadelphia if it were 'Always Sunny in Philadelphia'. We first model how the solar flux varies from the Sun to the Earth, then we investigate how the intensity of the flux varies depending on the Earth's orientation with respect to the Sun. We find that a sunny Philadelphia would recieve roughly 4 times as much solar flux.